Skin cancers in patients after organ transplantation - Imko-Walczuk, Beata; Ankudowicz, Anna; Jaśkiewicz, Janusz; Lizakowski, Sławomir; Dębska-Ślizień, Alicja; Rutkowski, Bolesław (Dermatology Review/Przegląd Dermatologiczny, 2012)
Introduction . Increased risk of skin cancers in patients after organ transplantation is well known and documented. Skin cancers – squamous cell carcinoma (SCC) and basal cell carcinoma (BCC) – are the most common cancers occurring in patients after renal transplantation and represent over 90% of all skin cancers observed in this population. Objective . The aim of the study was to determine the risk of skin cancer in the Polish population of patients after renal transplantation, and to look for new clinical data on renal transplant recipients with skin cancers. The final aim of the study was to propose methods of prophylaxis in order to prevent and early detect skin cancers in renal transplant recipients. Material and methods . Data on the incidence of skin cancers in a population of renal transplant recipients were collected and analyzed at the Medical University of Gdansk, Department of Plastic Surgery and Department of Nephrology, Transplantology and Internal Medicine. From 1980 until the end of 2008, 916 patients with end stage renal disease who underwent 1008 renal transplantations were analysed. In January 2009, under the care of the Clinic remained 704 patients. The study evaluating the incidence of skin cancers in a population of renal transplant patients included a total of 40 patients with skin cancer, which represent 4.33% of all patients, 25 patients (62.5%) were included prospectively and 15 patients (37.5 %) retrospectively. Age of patients for this group was in the range from 17 to 77 years (mean 49.4 years). Results . In 40 patients included into the study 58 skin cancers were diagnosed. Coefficient was obtained 3724.0 per 100,000 people, which gave 204.7-fold higher incidence of skin cancer compared to general population. Squamous cell carcinoma was much more aggressive in patients after renal transplantation than in immunocompetent patients. Longer development of skin cancers in younger patients, 10-12 years after renal transplantation suggests their formation as de novo mutations in skin cells. Conclusions . Our observations indicate the need of special care for patients receiving transplants at older age (> 50 years), to provide them regular dermatological control in a short time after renal transplantation. In this group it is necessary to pay a special attention to risk factors and recommend prophylactic methods in patient.